Words as powerful weapons: dysphemism in Trump’s Covid-19 speeches - Olimat, Sameer Naser (Penerbit Universiti Kebangsaan Malaysia, 2020)
Covid-19 pandemic constitutes the greatest threat to the worldwide population and countries nowadays. Donald Trump, the president of the greatest country in the world, has frequently received heavy criticism as a result of his language use in the period of Covid-19. Therefore, the present paper examines dysphemistic expressions used in Trump’s discourse on Covid-19. A sample of dysphemistic examples adopted in Trump’s daily speeches in a crucial week of 11th till 18th of March 2020 was analysed. The researcher relied on the Critical-political Discourse Analysis by Van Dijk (1997; 2001), Conceptual Metaphor theory by Lakoff and Johnson (1980), and the concept of dysphemism by Allan and Burridge (2006). It has been found that Trump referred to strong language and war metaphors to defend himself and his point of view, to shape Americans’ thoughts and views, or to attack other countries or institutions. Several conceptual metaphors, including Covid-19 is a) an invisible enemy, b) a foreign enemy, c) a dangerous threat, and d) a global battle, were commonly used. The data analysis shows that Trump has a linguistic mastery of eloquent and persuasive devices in political discourse which permitted him to make a shift in Americans’ thoughts and opinions. For future research, the current paper suggests investigating Trump’s paralinguistic features in speeches, such as body language, facial expressions, tone and pitch of voice, eye movements, and hand gestures.